Evaluation of safety in the system of air traffic - Харченко, В.П.; Чинченко, Ю.В.; Бабейчук, Д.Г.; Райчев, С.Г. (Proceedings of National Aviation University, 2007)
The areas, which should be analyzed at estimation of safety of Air Traffic Management system of Ukraine are determined. The methodology of ICAO and Eurocontrol to reveal and analyze the ACFT collision risk level at composing or re-organization of ATS routes is considered.